Implementing PERT for Capital Repairs of a Blast Furnace: A Comprehensive Approach (International Journal of Food and Nutritional Sciences, 2022)
The smooth operation of any industry or plant hinges on the seamless functioning of its various components. When a component or unit is not operational, it's termed as downtime, which is detrimental to production. Therefore, minimizing downtime is paramount from a production standpoint. To achieve this goal, modern maintenance techniques are utilized to proactively prevent any disruptions in operations.